MATHEMATICAL MODELING OF RADIATION DEFECT FORMATION PROCESSES ON LIGHT TARGETS - Shmygaleva, Tat'yana; Srazhdinova, Aziza (Journal of Mathematics, Mechanics and Computer Science, 2025)
The article analyzes the problem of studying the mechanisms of radiation defect generation in materials under ion irradiation. During the research, algorithms were developed to calculate the cascade-probability function (CPF) and the concentration of cascade regions as a function of the depth of the irradiated material, which allowed for an increase in the accuracy of modeling defect formation processes. The calculations of the CPF and the concentration of cascade regions revealed patterns in the behavior of radiation defects depending on the physical parameters of irradiation. The comparison of the obtained calculated data with experimental results confirmed the validity of the developed algorithms and models. A distinctive feature of the proposed method is the application of an analytical cascade-probability approach, which allows tracking the dynamics of defect formation at any depth of the target, unlike traditional numerical methods that require significant computational resources. These results can be explained by the fact that the process of particle interaction with matter and the formation of radiation defects is probabilistic, allowing for the determination of the probabilities of ion interactions with materials (CPF) at any depth of the irradiated material, which enables more accurate modeling of defect formation processes and their dependence on physical parameters such as energy and depth. The developed models and algorithms can be applied in materials science, micro- and nanoelectronics, and in predicting the radiation resistance of structural materials.